Relationship of maternal knowledge, practices and attitudes regarding oral health status in children aged 3 to 6 - Ortiz Cuayla, Diego Arturo (2024)
Objective: is to relate maternal knowledge, practices and attitudes about the state of Oral Health in children from 3 to 6 Method: It is analytical, correlational, observational, prospective, transversal and corresponds to a non-experimental design. For data collection, a structured questionnaire was applied to measure the knowledge, practices and skills of the mothers and an observation sheet to establish the oral health status of the students. A sample of 33 students from 3 to 6 years of age was used. Results: We observed that the level of knowledge of mothers has a statistically significant relationship with the health status of their children (ceo-d=3.82) with a P-value of 0.004; On the other hand, in practices and attitudes they did not show a statistically significant relationship, with a P-value of 0.263 and 0.07 respectively. Conclusion: The knowledge of mothers is related to the health status of their children, but not the practices and attitudes.